Progression of diabetic retinopathy after bariatric surgery. Issue 9 (26th February 2015) - Murphy, R.; Jiang, Y.; Booth, M.; Babor, R.; MacCormick, A.; Hammodat, H.; Beban, G.; Barnes, R. M.; Vincent, A. L.
Abstract Aim To assess the impact of bariatric surgery on the progression of diabetic retinopathy in patients with Type 2 diabetes. Method We conducted a retrospective, observational study of patients with Type 2 diabetes who underwent bariatric surgery between 1 January 2001 and 31 December 2012 and had hospital‐based retinal screening records. Data were collected from four surgical centres. Those who had pre‐operative retinal screening and at least one post‐operative retinal screen were eligible for analysis. A generalized linear mixed model was used to explore significant clinical predictors on the post‐operative grade severity over time, controlling for important baseline characteristics. Results Three hundred and eighteen patients were eligible for analysis. Of these, 68.6% had no diabetic retinopathy pre‐operatively compared with 18.9%, 8.5% and 4% with a diabetic retinopathy grade of minimal, mild or moderate and higher, respectively. First post‐operative retinal screening results showed that after surgery 73% had no change in their diabetic retinopathy grade, 11% regressed and 16% progressed. The probability of having a diabetic retinopathy grade of moderate or higher over time post surgery was significantly associated with the magnitude of HbA1c reduction from pre‐surgery HbA1c levels, a shorter post‐operative retinal screening duration, more severe pre‐operative retinal screening grade, male gender and non‐Maori/Pacific ethnicity. Conclusions A higher pre‐operative diabetic retinopathy grade, and a large decrease in HbA1c post surgery warrant closer monitoring of diabetic retinopathy after bariatric surgery. Further prospective, randomized studies are required to investigate the gender and ethnic differences found.